LEVEL OF SOCIAL ANXIETY AMONG ADOLESCENCE VISITING HAZARIBAG COLLEGE OF DENTAL SCIENCES AND HOSPITAL, JHARKHAND - Chatterjee, Silpi; Khan, Asim Mustafa; M Sibgatullah,; Daya Shankar,; Prasad, Raghu Ranjan; Jayesh Anand, (International Journal of Psychosocial Rehabilitation, 2020)
The student’s social anxiety is increasing in the world nowadays. More psychotic incidence of students, fatally wounding, kicking etc. Social anxiety is a disabling and treatable disorder with common onset in adolescents. It also a most psychological disorder in school aged children and adolescents worldwide. The objectives of the study were to assess the level of social anxiety among adolescence coming to our hospital for treatment, Hazaribag, Jharkhand. Descriptive research design was used among 60 adolescences with the age group of 12-18 years and non-probability convenient sampling was adopted for the study. The results showed that 20 (33.3 %) had mild level of social anxiety and 6 (10 %) of them had moderate level of social anxiety.